A critical narrative approach to openness : the impact of open development on structural transformation - Bentley, Caitlin Maureen (2021)
Openness has become an important, all‐encompassing term denoting activities facilitated by sharing, using, producing, and redistributing information and communication resources within digital information systems. We compare theoretical advancements that emphasize processes and characteristics of openness with the limitations of extant approaches that have largely focused on improvements to productivity and efficiency. Based on Foucault and Bruner's ideas, this paper contributes a new critical narrative approach to understanding openness explicitly focused on structural transformation and power. The analysis focuses on the case of open development, examining 20 key studies based primarily on developing countries. The critical narrative approach unpacked the production of power/knowledge across actors, intentions, and outcomes of openness research and practice. We find that discursive formations are reliant on technocentric and normative ideals of researchers, leading to narratives of hypothetical outcomes that exclude marginalized perspectives. We propose hermeneutic composability and contesting normative narratives of openness as analytical techniques for an integrated, mutually constitutive conception of interactions between individuals, open artefacts, and open social praxis.